Casting process of a crankshaft of a rotary air conditioner compressor

CN122918281APending Publication Date: 2026-10-16SHAOGUAN JINBAO FOUNDRY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611036532.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的之一在于提供一种转子式空调压缩机曲轴的铸造工艺,解决了现有球墨铸铁曲轴弹性模量偏低、强韧性难以兼顾的问题

Benefits of technology

(1)本发明突破常规球墨铸铁的成分设计思路,采用“近共晶碳当量—低硅—锰铜复合合金化”的成分方案,控制C 3.75~3.85%、Si 1.4~1.5%、Mn 0.4~0.7%、Cu 0.5~0.95%、S≤0.03%、P≤0.07%,配合1500~1550℃的熔炼出炉温度保证成分均匀与铁水质量;结合加入量为铁水质量1.0~1.2%、处理温度1480~1520℃的冲入法球化处理,以及分级孕育工艺,在保证良好铸造性能的前提下,使基体获得高含量的细片状珠光体组织与圆整均匀的球状石墨,实现了弹性模量与强度的同步提升,解决了现有技术中强度与塑性难以兼顾、弹性模量不足的技术难点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a casting process of a rotor type air conditioner compressor crankshaft and belongs to the technical field of precision casting. The process realizes accurate regulation and control of the crankshaft structure and mechanical properties by synergistically optimizing an alloy component system, controlling C 3.75~3.85%, Si 1.4~1.5%, Mn 0.4~0.7%, Cu 0.5~0.95%, matching with a balling treatment and a staged inoculation process by means of a punching method, and combining with a large-flow variable cross-section slag collection deceleration pouring system. The prepared nodular cast iron crankshaft has a spheroidization level of 1~2, a spheroidization rate of greater than or equal to 85%, graphite size of 6~8, and an average pearlite content of greater than or equal to 80% on a detection surface; the elastic modulus, tensile strength and elongation rate are well matched, and the performance process stability is excellent; the flexural deformation and friction power consumption of the crankshaft under high-speed operation can be effectively reduced, casting defects are reduced, the development requirements of miniaturization, high efficiency and low noise of the rotor type air conditioner compressor are met, and the process is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of precision casting technology, specifically relating to a casting process for a crankshaft of a rotary air conditioning compressor. Background Technology

[0002] With the continuous upgrading of my country's household appliance energy efficiency standards, rotary air conditioner compressors, with their core advantages of compact structure, small size, high energy efficiency ratio, and low manufacturing cost, have become the mainstream technology for household split air conditioners and small commercial air conditioners, and market demand continues to grow. Currently, the industry is rapidly developing towards miniaturization, high speed, high efficiency, and low noise, directly driving the performance upgrade of the core transmission component, the crankshaft.

[0003] The crankshaft is the core load-bearing and transmission component of a rotary compressor. Its upper end connects with the motor rotor to transmit torque, while its lower eccentric section drives the piston within the cylinder to complete the entire process of refrigerant intake, compression, and exhaust. During operation, the crankshaft simultaneously bears alternating torsional loads, bending loads, and frictional wear, resulting in complex operating conditions and large load fluctuations. As compressor displacement increases and overall size decreases, the crankshaft's length-to-diameter ratio continuously increases, making deflection a core bottleneck restricting performance improvement. The elastic modulus of conventional ductile iron crankshafts is generally around 150 GPa. With an increased length-to-diameter ratio, deflection increases exponentially, leading to uneven motor air gaps causing increased noise and vibration, accelerated wear resulting in increased frictional power consumption, and oil film failure causing abnormal wear and the risk of seizure. These factors directly affect the compressor's energy efficiency, operational reliability, and NVH performance.

[0004] Currently, there are three main technical routes for improving crankshaft performance in the industry, but all have significant limitations. The first is steel crankshaft replacement solutions. For example, patent application CN112814991A discloses a cold-forged crankshaft, and patent application CN117684158A discloses a manganese-based phosphating process for steel crankshafts. While these offer superior tensile strength and surface properties, steel materials have poor casting performance, weak vibration damping, long processing steps, and high overall costs. Furthermore, surface treatment only affects the surface layer and cannot address the fundamental problem of insufficient elastic modulus in the matrix, making it difficult to meet the comprehensive requirements of mass-produced models. The second is surface modification technologies such as diamond-like carbon coating and nitriding. These only improve surface hardness and wear resistance, failing to enhance the matrix stiffness and deformation resistance, and cannot fundamentally solve the crankshaft flexural deformation problem. The third is optimization of cast iron composition and casting process. Existing solutions often improve strength by adjusting carbon and silicon content or adding alloying elements, but these generally suffer from a mismatch between strength and toughness; high strength is often accompanied by a significant decrease in elongation.

[0005] In summary, existing technologies cannot simultaneously achieve a balance between high elastic modulus, high strength, high elongation, and high stability in ductile iron crankshafts. They cannot meet the multiple requirements of performance, cost, and reliability, thus becoming a technological bottleneck for the miniaturization and high efficiency upgrade of rotary compressors. Summary of the Invention

[0006] One of the objectives of this invention is to provide a casting process for a rotor-type air conditioning compressor crankshaft, which solves the problems of low elastic modulus and difficulty in balancing strength and toughness in existing ductile iron crankshafts.

[0007] The objective of this invention can be achieved through the following technical solutions: A casting process for a rotary air conditioning compressor crankshaft includes the following steps: S1 Batching and Smelting: Alloy raw materials are prepared according to mass percentage, with the following elemental composition: C 3.75~3.85%, Si 1.4~1.5%, Mn 0.4~0.7%, Cu 0.5~0.95%, S≤0.03%, P≤0.07%, and the balance being Fe and unavoidable impurities; the raw materials are added to the smelting furnace and smelted into molten iron, with the tapping temperature controlled at 1500~1550℃; S2 spheroidizing treatment: Spheroidizing treatment is carried out by the injection method. The amount of spheroidizing agent added is 1.0~1.2% of the mass of molten iron, and the spheroidizing treatment temperature is controlled at 1480~1520℃. S3 inoculation treatment: A graded inoculation process is adopted. The first inoculation is added during the spheroidizing treatment, and the amount added is 0.8~1.0% of the mass of molten iron; the in-flow inoculation is added during the casting process, and the addition rate is 3~5g / s. S4 casting: The casting is carried out using a high-flow-rate variable cross-section slag collection and deceleration casting system. The casting temperature is 1380~1420℃ and the single-mold casting time is 8~15s. S5 Shaking and Heat Treatment: After the casting cools, the sand is removed, cleaned, and then subjected to stress-relieving annealing to obtain the crankshaft casting.

[0008] At the compositional level, the carbon content is controlled within the near-eutectic range of 3.75-3.85%, combined with a low-silicon design of 1.4-1.5%, keeping the carbon equivalent near the eutectic point. This ensures good casting fluidity and filling capacity of the molten iron, reducing forming defects such as incomplete filling and cold shuts. Furthermore, it reduces the proportion of ferrite formation and promotes pearlite transformation, providing a dense matrix structure for high elastic modulus. Composite alloying is achieved by adding 0.4-0.7% manganese and 0.5-0.95% copper. Manganese stabilizes the pearlite structure and improves matrix strength, while copper refines the pearlite lamellar spacing and produces a solid solution strengthening effect. At this ratio, the two work synergistically to simultaneously improve the elastic modulus and tensile strength of the matrix without significantly sacrificing plasticity, solving the problem of difficulty in achieving both strength and toughness in conventional processes. Meanwhile, by controlling S to ≤0.03% and P to ≤0.07%, the destructive effect of harmful impurities on the matrix is ​​minimized. Combined with a smelting and tapping temperature of 1500~1550℃, the composition is made uniform and the quality of the molten iron is ensured, providing a qualified molten iron base for subsequent spheroidizing and inoculation processes.

[0009] The spheroidizing treatment adopts the flushing method, combined with the addition of 1.0~1.2% spheroidizing agent and a treatment temperature of 1480~1520℃. This ensures a sufficient supply of magnesium and rare earth spheroidizing elements, so that the graphite is fully spheroidized, minimizing the cutting effect of spheroidal graphite on the matrix and ensuring the isotropic and stable mechanical properties. At the same time, it avoids graphite distortion and cost increase caused by excessive spheroidizing agent, and controls the magnesium element burn-off within a reasonable range to ensure a stable and sufficient spheroidizing reaction.

[0010] The graded inoculation process combines primary inoculation with nucleation at a dosage of 0.8-1.0% and subsequent inoculation at a rate of 3-5 g / s to refine the graphite. This effectively avoids inoculation degradation, ensures uniform graphite morphology at different wall thicknesses in the casting, reduces performance fluctuations at the microstructure level, and improves the stability of batch production. The two-stage inoculation process is seamlessly integrated, balancing the long-term effectiveness of inoculation with the instantaneous strengthening effect before filling.

[0011] The use of a high-flow-rate variable cross-section slag collection and deceleration casting system, combined with a casting temperature of 1380~1420℃ and a single-mold casting time of 8~15s, reduces air entrapment and slag inclusions from the filling source, improves matrix density, and eliminates performance dispersion caused by micro-defects. This is a key technical means to improve process stability and reduce performance dispersion.

[0012] Finally, the casting undergoes a post-treatment process of cooling, sand removal, and stress-relief annealing to fully eliminate internal casting stress, stabilize the dimensional accuracy and microstructure of the casting, and prevent performance fluctuations and deformations during subsequent machining and service. These five interconnected steps, with coordinated parameter matching, work together to achieve a balance between high elastic modulus, high strength, and high stability in the crankshaft.

[0013] Furthermore, in step S1, the alloy composition, by mass percentage, is: C 3.78~3.82%, Si 1.42~1.48%, Mn 0.45~0.55%, Cu 0.75~0.95%, S≤0.02%, P≤0.06%. Adopting a medium-manganese, high-copper ratio increases the proportion of copper, which better refines the pearlite lamellars. While ensuring strength and elastic modulus, it better maintains the material's plasticity and toughness, making it suitable for thin-walled crankshaft products with higher requirements for elongation and impact resistance.

[0014] Furthermore, in step S1, the alloy composition, by mass percentage, is: C 3.78~3.82%, Si 1.42~1.48%, Mn 0.62~0.68%, Cu 0.62~0.68%, S≤0.02%, P≤0.06%. Increasing the proportion of manganese can further improve the pearlite content and thermal stability, making it more suitable for thick-walled, large-displacement crankshaft products with higher requirements for strength and elastic modulus and sufficient plasticity allowance.

[0015] Furthermore, in step S2, the spheroidizing agent is a rare earth magnesium-silicon-iron spheroidizing agent, which, by mass percentage, contains 7-9% Mg, 1-3% Re, and 40-45% Si, with the remainder being Fe and trace impurities. Magnesium, as the core spheroidizing element, ensures the graphite spheroidizing effect, while rare earth elements assist in purifying molten iron, removing oxygen and sulfur impurities, and improving graphite sphericity. A low rare earth ratio can control raw material costs while ensuring spheroidizing quality, and avoid graphite distortion and increased brittleness caused by excessive rare earth.

[0016] Furthermore, in step S3, the primary inoculant is a silicon-barium-calcium inoculant, wherein, by mass percentage, the Si content is 60-65%, the Ba content is 4-6%, and the Ca content is 1-2%; the in-flow inoculant is a silicon-strontium inoculant, wherein, by mass percentage, the Si content is 70-75% and the Sr content is 0.8-1.2%. The silicon-barium-calcium inoculant possesses long-lasting inoculation properties, maintaining the inoculation effect from spheroidization to casting for an extended period and inhibiting spheroidization decay; the silicon-strontium inoculant has strong graphitization ability and good graphite refinement effect, adapting to the process characteristics of in-flow late inoculation. The combination of these two inoculants achieves stable coverage of the inoculation effect throughout the entire process.

[0017] Furthermore, in step S4, the high-flow-rate variable cross-section slag-collecting and decelerating casting system includes a pouring cup, a sprue, a runner, and an ingate connected in sequence. The runner has a variable cross-section structure along the direction of molten iron flow, with an inlet cross-section to outlet cross-section area ratio of 1.5 to 2:1, and at least two slag-collecting baffles are provided within the runner. The ingate is located at the bottom of the runner, with a total area ratio of the ingate to the sprue cross-section of 1.2 to 1.5:1. The variable cross-section runner gradually reduces the molten iron flow rate, facilitating the floating of low-density slag inclusions to the liquid surface; the slag-collecting baffles physically intercept suspended inclusions, achieving secondary purification; the bottom-pouring ingate achieves stable mold filling, reducing splashing and air entrapment; the three components work together to reduce casting defects from multiple dimensions and improve matrix density.

[0018] Furthermore, the sprue has a tapered structure, wider at the top and narrower at the bottom, with a taper of 1:50 to 1:40; a ceramic filter is installed at the bottom of the pouring cup, with a pore size of 10 to 20 ppi. The tapered sprue ensures that the mold is always filled with molten iron during the filling process, preventing air from being drawn in by negative pressure; the ceramic filter can initially filter large particles of molten slag, forming a multi-stage purification system with the slag collection function of the horizontal sprue.

[0019] Furthermore, the height of the slag-collecting baffles is 2 / 3 to 3 / 4 of the height of the horizontal gating channel, and they are arranged at intervals along the direction of molten iron flow. Limiting the height parameter of the slag-collecting baffles ensures effective interception of floating slag inclusions while avoiding excessively high baffles that could cause turbulent flow and air entrapment in the molten iron, thus balancing the slag collection effect with the stability of the mold filling process.

[0020] Furthermore, in step S5, the stress-relief annealing process is as follows: the temperature is raised to 500-550℃ at a rate of 50-80℃ / h, held for 2-4 hours, and then cooled in the furnace to below 200℃ before being air-cooled. This temperature range can fully eliminate casting internal stress without changing the pearlite matrix structure. The slow heating and cooling can avoid generating new thermal stress, ensuring the long-term stability of the casting's dimensions and performance.

[0021] Furthermore, after pouring in step S4, the casting should be cooled in the sand mold for no less than 120 minutes, and the casting temperature should not exceed 400℃ when the sand is removed. Sufficient in-mold cooling can avoid the risk of casting deformation and cracking caused by high-temperature sand removal, and ensure the stability of the casting's structure and dimensions.

[0022] The beneficial effects of this invention are: (1) This invention breaks through the conventional composition design concept of ductile iron and adopts the composition scheme of "near eutectic carbon equivalent - low silicon - manganese copper composite alloying". It controls C 3.75~3.85%, Si 1.4~1.5%, Mn 0.4~0.7%, Cu 0.5~0.95%, S≤0.03%, P≤0.07%, and ensures uniform composition and molten iron quality by using a melting and tapping temperature of 1500~1550℃. Combined with the spheroidizing treatment by the injection method with an addition amount of 1.0~1.2% of the molten iron mass and a treatment temperature of 1480~1520℃, as well as the graded inoculation process, under the premise of ensuring good casting performance, the matrix obtains a high content of fine lamellar pearlite structure and round and uniform spheroid graphite, realizing the simultaneous improvement of elastic modulus and strength, and solving the technical difficulties of the prior art in which strength and plasticity are difficult to balance and elastic modulus is insufficient.

[0023] (2) The present invention adopts a graded control method that combines one-time inoculation with in-flow inoculation at an addition rate of 3-5 g / s, which effectively solves the problems of inoculation decline and insufficient inoculation in thin-walled parts in traditional processes. This makes the graphite morphology uniform and consistent at different wall thicknesses of the crankshaft, with a stable spheroidization level of 1-2 and a graphite size of 6-8. At the same time, with the high flow rate and variable cross-section slag collection and deceleration casting system, under the parameter matching of casting temperature of 1380-1420℃ and single mold casting time of 8-15s, the range of mechanical property fluctuation is reduced from both the aspects of microstructure uniformity and matrix density, so that the process capability index CPL of elastic modulus can be stably reached above 1.33.

[0024] (3) The high-flow-rate variable cross-section slag collection and deceleration casting system designed in this invention integrates multiple functions such as ceramic filtration, variable cross-section deceleration, baffle slag collection, and bottom pouring for stable filling. With appropriate casting temperature and casting time, it reduces air entrapment and slag inclusions from the source, reducing the porosity and slag inclusion defect rate of castings from more than 3% to less than 0.5%. The improvement in matrix density not only directly increases the average elastic modulus, but also eliminates the performance dispersion caused by internal defects, thereby improving the process capability index.

[0025] (4) The casting process of the present invention can be directly implemented on existing casting production lines with clay sand molding and medium-frequency melting. The parameters of the entire process, from melting and batching, spheroidizing inoculation, casting and molding to sand removal and stress-relief annealing, are all compatible with conventional mass production equipment. No new large-scale equipment investment is required. Product performance can be upgraded simply by optimizing the composition and process parameters. After the casting cools, the sand is removed and then stress-relief annealing is performed, which can fully eliminate the internal stress of casting and stabilize the dimensional accuracy and microstructure of the casting. Compared with steel crankshafts, the ductile iron crankshaft of the present invention has significant advantages such as good casting performance, excellent vibration damping, small machining allowance, and low overall cost, making it more suitable for large-scale industrial mass production. Detailed Implementation

[0026] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0027] Example 1 This embodiment provides a casting process for a single-cylinder crankshaft of a rotary air conditioning compressor, and the specific steps are as follows: Batching and Smelting: The alloy composition is prepared according to the following mass percentages: C 3.80%, Si 1.45%, Mn 0.50%, Cu 0.85%, S 0.018%, P 0.05%, with the balance being Fe and unavoidable impurities. The raw materials are added to a 1-ton medium-frequency induction melting furnace for melting, heated to 1520℃, held for 8 minutes, and the composition is tested and fine-tuned to the target range before being tapped out of the furnace.

[0028] Spheroidizing treatment: Spheroidizing is performed using a dam-type ladle pouring method. The spheroidizing agent is a rare earth magnesium-silicon-iron spheroidizing agent (Mg 8.0%, Re 2.0%, Si 42%), added at 1.1% of the molten iron mass. An inoculant and a clean iron filings protective layer are sequentially applied to the spheroidizing agent. The initial spheroidizing temperature is 1500℃, and the slag is immediately removed after the reaction is complete.

[0029] Inoculation treatment: For primary inoculation, a silicon-barium-calcium inoculant (Si 62%, Ba 5%, Ca 1.5%) is added at a rate of 0.9% of the molten iron mass and placed in the ladle dam along with the spheroidizing agent; for in-flow inoculation, a silicon-strontium inoculant (Si 72%, Sr 1.0%) is added via a screw-type in-flow inoculation device at a rate of 4 g / s.

[0030] Casting: A high-flow-rate, variable-section slag-collecting, decelerating casting system is used for wet sand casting. A 15ppi ceramic filter is embedded at the bottom of the pouring cup; the sprue is conical with a taper of 1:45; the inlet-to-outlet cross-sectional area ratio of the runner is 1.8:1, and it contains two slag-collecting baffles, each baffle height being 2 / 3 of the runner height; the ingate is located at the bottom of the runner, with a total area ratio of 1.3:1 to the sprue cross-sectional area. The casting temperature is 1400℃, and the single-mold casting time is 10 seconds.

[0031] Sand removal and heat treatment: The casting is kept in the sand mold for 150 minutes and removed from the sand when the temperature drops to 350℃. After shot blasting and grinding, stress-relieving annealing is carried out: the temperature is raised to 520℃ at 60℃ / h, held for 3 hours, and then cooled to 180℃ in the furnace before being air-cooled to obtain the finished crankshaft.

[0032] Example 2 The only difference between this embodiment and Example 1 is the alloy composition, which is: C 3.80%, Si 1.45%, Mn 0.65%, Cu 0.65%, S 0.018%, P 0.05%, with the balance being Fe and unavoidable impurities. All other process steps, parameters, and equipment are exactly the same as in Example 1.

[0033] Example 3 The only difference between this embodiment and Example 1 is the alloy composition, which is: C 3.76%, Si 1.42%, Mn 0.45%, Cu 0.90%, S 0.015%, P 0.045%, with the balance being Fe and unavoidable impurities. All other process steps, parameters, and equipment are exactly the same as in Example 1.

[0034] Example 4 The difference between this embodiment and Embodiment 1 lies in the adjustment of process parameters: the smelting furnace exit temperature is 1530℃; the amount of spheroidizing agent added is 1.0% of the molten iron mass, and the initial spheroidizing treatment temperature is 1510℃; the amount of primary inoculant added is 0.85% of the molten iron mass, and the in-flow inoculation rate is 3.5 g / s; the casting temperature is 1410℃, and the single-mold casting time is 9 s; the stress-relief annealing temperature is 530℃, and the holding time is 2.5 h. All other components and process details are exactly the same as in Embodiment 1.

[0035] Example 5 The difference between this embodiment and Embodiment 1 lies in the adjustment of the casting system parameters: the ratio of the inlet to outlet cross-sectional area of ​​the horizontal runner is 1.5:1, with three slag-collecting baffles inside, the height of which is 3 / 4 of the height of the horizontal runner; the taper of the sprue is 1:50; the pore size of the filter plate in the pouring cup is 10 ppi; and the ratio of the total area of ​​the ingate to the cross-sectional area of ​​the sprue is 1.2:1. All other components and process details are exactly the same as in Embodiment 1.

[0036] Example 6 This embodiment describes the casting process for a twin-cylinder crankshaft. The differences from Embodiment 1 are: the pouring temperature is 1390℃, the single-mold pouring time is 12s; the in-mold cooling time is 180min, the sand removal temperature is 320℃; the stress-relief annealing heating rate is 50℃ / h, and the holding time is 4h. All other components and process details are identical to those in Embodiment 1.

[0037] Comparative Example 1 This comparative example represents the standard industry-standard ductile iron crankshaft casting process, with the following specific parameters: The alloy composition is: C 3.90%, Si 2.20%, Mn 0.30%, Cu 0.40%, S 0.025%, P 0.06%, with the balance being Fe.

[0038] The spheroidizing treatment uses a conventional rare earth magnesium spheroidizing agent, with an addition amount of 1.2%; only 75% ferrosilicon is used for one-time inoculation, with an addition amount of 1.0%, and there is no in-flow inoculation.

[0039] It adopts a conventional constant cross-section casting system with a constant cross-sectional area of ​​the horizontal sprue, no slag baffles, no ceramic filter plates, and top-filling molding.

[0040] The pouring temperature was 1400℃, and the sand removal and heat treatment processes were the same as in Example 1.

[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is the casting system: a conventional equal-section casting system is used, with a constant cross-sectional area of ​​the horizontal runner, no slag baffles, no ceramic filter plates, and top-filling. The remaining alloy composition, spheroidizing process, inoculation process, and heat treatment process are exactly the same as those in Example 1.

[0042] Comparative Example 3 The only difference between this comparative example and Example 1 is that the alloy composition deviates from the scope of this invention. Specifically, the composition is: C 3.70%, Si 1.60%, Mn 0.80%, Cu 0.45%, S 0.020%, P 0.06%, with the balance being Fe and unavoidable impurities. All other process steps, parameters, and equipment are exactly the same as in Example 1.

[0043] Comparative Example 4 The only difference between this comparative example and Example 1 is the inoculation process: only silicon-barium-calcium inoculation is used, with an addition amount of 0.9% of the molten iron mass, and no in-flow inoculation; the remaining alloy composition, spheroidizing process, casting system, and heat treatment process are exactly the same as in Example 1.

[0044] Performance Tests and Results 1. Chemical composition analysis: The composition of the original molten iron was analyzed using a direct-reading spectrometer. Each sample was analyzed three times and the average value was taken.

[0045] 2. Metallographic structure test: Samples were taken from the center of the crankshaft main shaft and metallographic specimens were prepared in accordance with GB / T9441-2009 "Metallographic Examination of Ductile Iron". The spheroidization level, graphite size and pearlite content were observed and evaluated under an optical microscope.

[0046] 3. Mechanical property testing: Samples were taken from the crankshaft body and machined into φ10mm standard tensile test bars. Tensile tests were conducted on a universal testing machine according to GB / T228.1-2010 "Metallic materials - Tensile testing - Part 1: Test method at room temperature" to determine the tensile strength and elongation after fracture. The elastic modulus was determined according to GB / T22315-2008 "Metallic materials - Test method for elastic modulus and Poisson's ratio". The elastic modulus value was calculated by taking the elastic linear segment of 50~200MPa in the tensile stress range and using the axial force-deformation curve.

[0047] 4. Process Capability Index (CPL) Calculation: For the continuous production of 30 crankshafts of the same model, the elastic modulus of each crankshaft is sampled and tested. The mean and range analysis is performed using the XR control chart method to calculate the process capability index (CPL). The calculation formula is as follows: CPL=(μ-LSL) / 3-σ in, m The value represents the average elastic modulus of 30 samples, and LSL is the lower limit of specification (160 GPa). s This represents the process standard deviation.

[0048] 5. Casting defect rate detection: Fluorescent magnetic particle testing is used to detect surface defects of the crankshaft, and the internal porosity and slag inclusion defects are detected by dissection method. The percentage of castings with defects exceeding the standard is counted and the defect rate is calculated.

[0049] The results are shown in Table 1: Table 1

[0050] As shown in Table 1, all performance indicators of Examples 1-6 reached excellent levels: the spheroidization level was stable at 1-2, the graphite size was 6-8, and the average pearlite content was above 83%; the average elastic modulus was above 162 GPa, with a maximum of 165.5 GPa; the average tensile strength was above 770 MPa, with a maximum of 798 MPa; the average elongation was above 4.5%, achieving a good match between high strength and high plasticity; the elastic modulus CPL value was above 1.46, showing excellent performance stability; and the casting defect rate was below 0.5%, far below the industry standard.

[0051] Comparative Example 1 uses industry-standard high-silicon low-alloy composition and simple process, resulting in low spheroidization level, coarse graphite, and pearlite content of only 62%, leading to an elastic modulus of only 148.5 GPa and tensile strength of only 620 MPa, which are far lower than those of the embodiments of the present invention; moreover, the defect rate is as high as 3.5%, the performance fluctuates greatly, and the CPL value is only 0.72, which is completely unable to meet the performance requirements of high-end compressors.

[0052] Comparative Example 2 uses the composition and spheroidizing inoculation process of the present invention, but uses a conventional equal cross-section casting system. Its metallographic structure is similar to that of the embodiment of the present invention, but due to the large number of defects such as pores and inclusions (defect rate 2.8%), the elastic modulus and tensile strength are significantly reduced, and the performance dispersion is increased. The CPL value is only 1.05, which does not meet the process capability requirement of 1.33.

[0053] Comparative Example 3 retains the complete process system of the present invention, but the alloy composition deviates from the protection scope of the present invention. The carbon content is low, the silicon and manganese content is high, and the copper content is low, resulting in an elongation of only 3.2%, insufficient toughness, and easy brittle fracture. At the same time, the pearlite content, elastic modulus, and tensile strength are all lower than those of the embodiments of the present invention, and the CPL value is less than 1.0.

[0054] Comparative Example 4 retained the composition system and casting system of the present invention, but eliminated in-flow inoculation and adopted only one inoculation. Its spheroidization level dropped to level 2, the graphite size uniformity decreased, the pearlite content also decreased, and the final elastic modulus and tensile strength declined. Moreover, the performance dispersion increased significantly, and the CPL value was only 1.18, which could not meet the process capability requirement of 1.33.

[0055] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.

Claims

1. A casting process for a crankshaft of a rotary air conditioning compressor, characterized in that, Includes the following steps: S1 Batching and Smelting: Alloy raw materials are prepared according to mass percentage, with each element having the following composition: C 3.75~3.85%, Si 1.4~1.5%, Mn 0.4~0.7%, Cu 0.5~0.95%, S≤0.03%, P≤0.07%, and the balance being Fe and unavoidable impurities; the raw materials are added to the smelting furnace and smelted into molten iron, with the tapping temperature controlled at 1500~1550℃; S2 spheroidizing treatment: Spheroidizing treatment is carried out by the injection method. The amount of spheroidizing agent added is 1.0~1.2% of the mass of molten iron, and the spheroidizing treatment temperature is controlled at 1480~1520℃. S3 inoculation treatment: A staged inoculation process is adopted, with the inoculation done in one step during the spheroidizing treatment, and the amount added is 0.8~1.0% of the molten iron mass; The in-flow inoculation is added during the pouring process at a rate of 3-5 g / s. S4 casting: The casting is carried out using a high-flow-rate variable cross-section slag collection and deceleration casting system. The casting temperature is 1380~1420℃ and the single-mold casting time is 8~15s. S5 Shaking and Heat Treatment: After the casting cools, the sand is removed, cleaned, and then subjected to stress-relieving annealing to obtain the crankshaft casting.

2. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S1, the alloy composition by mass percentage is: C 3.78~3.82%, Si 1.42~1.48%, Mn 0.45~0.55%, Cu 0.75~0.95%, S≤0.02%, P≤0.06%.

3. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S1, the alloy composition by mass percentage is: C 3.78~3.82%, Si 1.42~1.48%, Mn 0.62~0.68%, Cu 0.62~0.68%, S≤0.02%, P≤0.06%.

4. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S2, the spheroidizing agent is a rare earth magnesium silicon iron spheroidizing agent, which, by mass percentage, contains 7-9% Mg, 1-3% Re, 40-45% Si, and the balance is Fe and trace impurities.

5. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S3, the primary inoculant is a silicon-barium-calcium inoculant, wherein the Si content is 60-65%, the Ba content is 4-6%, and the Ca content is 1-2% by mass percentage; the in-flow inoculant is a silicon-strontium inoculant, wherein the Si content is 70-75% and the Sr content is 0.8-1.2% by mass percentage.

6. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S4, the high-flow-rate variable cross-section slag-collecting and decelerating casting system includes a pouring cup, a straight pouring channel, a horizontal pouring channel, and an inner pouring channel connected in sequence; the horizontal pouring channel has a variable cross-section structure along the direction of molten iron flow, with an inlet cross-section to outlet cross-section area ratio of 1.5 to 2:1, and at least two slag-collecting baffles are provided in the horizontal pouring channel; the inner pouring channel is located at the bottom of the horizontal pouring channel, and the ratio of the total area of ​​the inner pouring channel to the cross-sectional area of ​​the straight pouring channel is 1.2 to 1.5:

1.

7. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 6, characterized in that, The sprue has a tapered structure that is wider at the top and narrower at the bottom, with a taper of 1:50 to 1:40; a ceramic filter is installed at the bottom of the pouring cup, with a pore size of 10 to 20 ppi.

8. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 6, characterized in that, The height of the slag collection baffle is 2 / 3 to 3 / 4 of the height of the horizontal pouring channel, and they are arranged at intervals along the direction of molten iron flow.

9. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, In step S5, the stress-relief annealing process is as follows: the temperature is raised to 500-550℃ at a rate of 50-80℃ / h, held for 2-4h, and then cooled in the furnace to below 200℃ before being air-cooled.

10. The casting process of the crankshaft of the rotary air conditioning compressor according to claim 1, characterized in that, After pouring in step S4, the casting shall be cooled in the sand mold for no less than 120 minutes, and the casting temperature shall not exceed 400℃ when it is removed from the sand.

Citation Information

Patent Citations

  • Crankshaft, machining process of crankshaft and rotor type compressor

    CN112814991A

  • Steel crankshaft surface treatment process and compressor

    CN117684158A